A case study in the growth performance of pineapple (MD2) intercropping with different rubber species / Nik Mohamad Amershazwan Nik Azlan - Nik Azlan, Nik Mohamad Amershazwan (Faculty of Plantation and Agrotechnolog, 2018)
Rubber tree is one of major crop in Malaysia since the old day. During the replanting season for rubber tree and the immature stage of rubber the farmer has zero income from it. It is because during that period rubber tree cannot be tapping. So, by doing the intercropping the problem with income can be solved. This case study is to see the growth performance of pineapple crop (MD2) when it intercropped with seven rubber species. During this study the primary data of pineapple growth were collected based on parameter which is height, number of leaves, length of leaves and leaf area. The data is collected at Jelebu Negeri Sembilan and the duration of study is February to May. The result is show that there a significant different with all the parameter on pineapple growth performance when intercrop with seven rubber species. The highest growth performance is pineapple intercrop with Hevea.benthamiana and the poor growth performance is pineapple intercrop with RRIM 600. There are certain characteristic of this species that make the effect toward the pineapples differ from each other Based on result, the conclusion can be make is there are rubber species that affect the growth performance of pineapple tree.